2021
DOI: 10.3390/antiox10091457
|View full text |Cite
|
Sign up to set email alerts
|

Positive Interaction between H2O2 and Ca2+ Mediates Melatonin-Induced CBF Pathway and Cold Tolerance in Watermelon (Citrullus lanatus L.)

Abstract: Cold stress is a major environmental factor that detrimentally affects plant growth and development. Melatonin has been shown to confer plant tolerance to cold stress through activating the C-REPEAT BINDING FACTOR (CBF) pathway; however, the underlying modes that enable this function remain obscure. In this study, we investigated the role of H2O2 and Ca2+ signaling in the melatonin-induced CBF pathway and cold tolerance in watermelon (Citrullus lanatus L.) through pharmacological, physiological, and genetic ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 66 publications
0
11
0
3
Order By: Relevance
“…Recent studies have further shed new light on the role of ROS in melatonin-regulated tolerance to abiotic stresses in plants. In early responses to cold stress, melatonin was found to stimulate H 2 O 2 accumulation in watermelon [ 98 ]. Chen et al found that endogenous melatonin rapidly induced ROS accumulation under short-term salinity treatment in Arabidopsis [ 12 ].…”
Section: Plant Abiotic Stress Tolerance Is Mediated By the Crosstalk ...mentioning
confidence: 99%
“…Recent studies have further shed new light on the role of ROS in melatonin-regulated tolerance to abiotic stresses in plants. In early responses to cold stress, melatonin was found to stimulate H 2 O 2 accumulation in watermelon [ 98 ]. Chen et al found that endogenous melatonin rapidly induced ROS accumulation under short-term salinity treatment in Arabidopsis [ 12 ].…”
Section: Plant Abiotic Stress Tolerance Is Mediated By the Crosstalk ...mentioning
confidence: 99%
“…Both the exogenous application of melatonin and the upregulation of endogenous melatonin through genetic modification have been found to enhance plant stress resistance. Across a variety of plants, including apple trees, grapevines, corn, sunflowers, tomato plants, watermelon, and wheat, melatonin has been found to increase antioxidant enzyme activity, alleviate oxidative stress and damage, delay cellular senescence, maintain intracellular redox homeostasis, and alter patterns of gene expression related to hormone metabolism and signal transduction [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Melatonin appears to also be crucial for immune response regulation, lateral root development, flowering phenology, and postharvest shelf-life prolongation.…”
Section: Introductionmentioning
confidence: 99%
“…Гіпотермія. За обробки мелатоніном підвищувалась холодостійкість рослин кавуна [27]. Цей ефект супроводжувався посиленням експресії генів CBF 1, COR 47, CIERD 10 та ін.…”
unclassified
“…Водночас у літературі є відомості, які, навпаки, вказують на підвищення активності НАДФН-оксидази під впливом мелатоніну і залучення АФК як посередників у шляхи передачі його сигналів [27]. Зокрема показано, що підвищення холодостійкості рослин кавуна мелатоніном, пов'язане з активацією експресії генів транскрипційних факторів родини CBF, супроводжувалося посиленням генерування H 2 O 2 , пов'язаним з активацією експресії гена каталітичної субодиниці НАДФН-оксидази RbohD.…”
unclassified
See 1 more Smart Citation